Effect of different high altitudes on vascular endothelial function in healthy people. Issue 11 (March 2020) - Fan, Ning; Liu, Cun; Ren, Ming
Abstract: Background: The aim of the study was to provide a theoretical basis for the early diagnosis and prediction of acute altitude sickness, to provide a better entry mode for healthy people from plain areas to plateau areas, and to preliminarily clarify the possible mechanism of this approach. Methods: We measured endothelin-1 (ET-1), asymmetric dimethylarginine (ADMA), vascular endothelial growth factor (VEGF), nitric oxide (NO), and hypoxia-inducible factor 1 (HIF-1) levels in each sample and determined flow-mediated dilation (FMD) values using a portable OMRON color Doppler with a 7.0- to 12.0-MHz linear array probe. We used the Lewis Lake score to diagnose acute mountain sickness (AMS) and to stratify the disease severity. Results: We found no cases of AMS at any of the studied elevation gradients. We found significant differences in FMD values between individuals when at 400 m above sea level and when at 2200, 3200, and 4200 m above sea level ( P < .05) but found no significant differences among those at 2200, 3200, and 4200 m. Our variance analysis showed that serum ET-1, VEGF, ADMA, NO, and HIF-1 levels in individuals at ≥3000 m and those at subplateau and plain areas (<3000 m) significantly differed ( P < .05). The level of these factors also significantly differed between individuals at elevation gradients of plateau areas (3260 m vs 4270 m) ( P < .05). We found no significant differences in serum ET-1, VEGF, and ADMA levels between individuals at the plateau (2260 m) and plain (400 m) areas ( P > .05). NO and HIF-1 levels were significantly different in serum samples from individuals between the plateau (2260 m) and plain (400 m) areas ( P < .05). However, with increasing altitude, the NO level gradually increased, whereas ET-1, ADMA, VEGF, and HIF-1 levels showed a decreasing trend. With the increase of altitude, there is no correlation between the trend of FMD and hematologic-related factors such as VEGF, NO, and HIF-1. Conclusion: A healthy young male population ascending to a high-altitude area experiences a low incidence of AMS. Entering an acute plateau exposure environment from different altitude gradients may weaken the effect of acute highland exposure on vascular endothelial dysfunction in healthy individuals. Changes in serum ET-1, VEGF, ADMA, NO, and HIF-1 levels in healthy young men may be related to the body's self-regulation and protect healthy individuals from AMS. A short stay in a subplateau region may initiate an oxygen-free preconditioning process in healthy individuals, thereby protecting them from AMS. Noninvasive brachial artery endothelial function test instead of the detection of invasive hematologic-related factors for early diagnosis and prediction of the occurrence and severity of acute high-altitude disease is still lack of sufficient theoretical basis.